1999
DOI: 10.3109/07357909909032872
|View full text |Cite
|
Sign up to set email alerts
|

Activities of DNA Turnover and Free Radical Metabolizing Enzymes in Cancerous Human Prostate Tissue

Abstract: Activities of adenosine deaminase (ADA), 5'nucleotidase (5'NT), xanthine oxidase (XO), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) and levels of thiobarbituric acid reagent substances (TBARS) were measured in 10 cancerous and 10 noncancerous human prostate tissues. Decreased activities of DNA turnover enzymes (ADA and 5'NT), increased activities of GSH-Px and CAT, and unchanged activities of SOD and XO were observed in cancerous prostate tissues compared with those of noncan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 36 publications
2
19
1
Order By: Relevance
“…Observations similar to our findings have been reported in human colorectal cancer [29], lung cancer [30], colorectal adenocarcinomas [31], human malignant tumors of the kidney [32] and prostate cancer [33]. However, this does not agree with the results obtained on tissue MDA levels in OSCC, as studied by Balasenthil et al [34 ]and Saroja et al [35].…”
Section: Discussioncontrasting
confidence: 54%
“…Observations similar to our findings have been reported in human colorectal cancer [29], lung cancer [30], colorectal adenocarcinomas [31], human malignant tumors of the kidney [32] and prostate cancer [33]. However, this does not agree with the results obtained on tissue MDA levels in OSCC, as studied by Balasenthil et al [34 ]and Saroja et al [35].…”
Section: Discussioncontrasting
confidence: 54%
“…the higher the rate of lipid peroxidation in the cells the lower the rate of cell division. [26] Our findings were in agreement with the reports of Biri et al; [27] Yilmaz et al, [28] who have reported increased TBARS concentrations suggesting oxidative stress and accelerate peroxidative reactions in the cancerous prostate tissues, even though antioxidant defense mechanisms were activated. However, DogruAbbasoglu et al [29] have found no significant change in lipid peroxidation or antioxidant system parameters in the plasma of patients with BPH and prostate cancer.…”
Section: Applicationssupporting
confidence: 93%
“…The specific activity of ADA in cancerous human prostate has been reported to be similar or slightly less than in normal prostatic tissue (36,37). However, ADA levels in benign prostatic hypertrophy (BPH) tissue were significantly higher than in normal prostate (36).…”
Section: Discussionmentioning
confidence: 92%